2016
DOI: 10.1108/nfs-07-2015-0085
|View full text |Cite
|
Sign up to set email alerts
|

Camel milk: alternative milk for human consumption and its health benefits

Abstract: Purpose – Camel as a livestock plays an important role in desert ecosystem and its milk has potential contribution in human nutrition in the hot and arid regions of the world. This milk contains all the essential nutrients as found in other milk. Fresh and fermented camel milk has been used in different regions in the world including India, Russia and Sudan for human consumption as well as for treatment of a series of diseases such as dropsy, jaundice, tuberculosis, asthma and leishmaniasis or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(55 citation statements)
references
References 30 publications
2
51
0
2
Order By: Relevance
“…Until now, camel milk seems to be the most appropriate substitute for cow milk, mainly because of the high proportion of β‐casein, low proportion of α‐casein, deficiency in ALA, and similarity of the Ig (Kumar and others ). Camel milk shows the lowest level of similarity (about 60%) with cow milk proteins (Jarvinen and Chatchatee ; Restani and others ; Tsabouri and others ).…”
Section: Cross‐reactivity Of Milk Allergensmentioning
confidence: 99%
“…Until now, camel milk seems to be the most appropriate substitute for cow milk, mainly because of the high proportion of β‐casein, low proportion of α‐casein, deficiency in ALA, and similarity of the Ig (Kumar and others ). Camel milk shows the lowest level of similarity (about 60%) with cow milk proteins (Jarvinen and Chatchatee ; Restani and others ; Tsabouri and others ).…”
Section: Cross‐reactivity Of Milk Allergensmentioning
confidence: 99%
“…The study proposes that camel milk intake could be significantly important to decrease the oxidative stress through changing the concentration of anti-oxidative enzymes non-enzymatic anti-oxidants molecules, hence reduced the signs of autism in children [58]. Also, lower content of B-casein, lack of B-lactoglobulin and presence of protective protein make camel milk suitable for to maintain immune system and brain development [59]. It has been stated that autism is among the diseases that has successfully healed with camel milk [60].…”
Section: Camel Milk and Anti-inflammatory Activitymentioning
confidence: 99%
“…Camel milk is considered a good source of protein, with a protein content of 3.00-3.90%. Caseins, including β-casein (65%) and whey proteins (20-25%), are the major proteins in camel milk [9]. Additionally, camel milk is characterised by high levels of vitamins (0.50-2.50%) and minerals (0.60-0.90%).…”
Section: Introductionmentioning
confidence: 99%
“…Iron (0.21-0.29 mg/100 g), sodium (58-59 mg/100 g), zinc (0.19-0.53 mg/100 g), potassium (156-179 mg/100 g), magnesium (10.40-14.00 mg/100 g), and cholesterol (3.00-5.00 g/kg of milk fat; low content) are also found in camel milk [10][11][12]. Several studies on camel milk have identified various health benefits, such as anticarcinogenic, antidiabetic, and antiviral effects [9,13]. Camel milk is a good choice for children allergic to bovine milk [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation